Workpiece and media tracking in barrel finishing. (22nd July 2009) - Boschetto, Alberto; Veniali, Francesco
The 2D kinetics of the workpiece during barrel finishing operation is studied. A particle image tracking technique was applied to a transparent thin barrel in order to acquire the position of the part within granular flow in rolling regime. The use of industrial near shape media leads to an intrinsic difficulty to trace the part position. The achieved trajectories permit to calculate the active working time, part density distribution, the media velocity gradient and the workpiece to media velocity gradient. These information are useful to calculate the total sliding and to get information about strain stress over part in order to investigate operation efficiency.